The diversity and epidemiology of Botryosphaeriaceae species associated with grapevines and woody hosts surrounding vineyards in South Africa - Du Plessis, Ihan Lambert (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.